How to grade for learning : linking grades to standards - O'Connor, Ken. (Thousand Oaks, California : c)
With more than 50,000 books sold, this resource for teachers and school teams will open illuminating and productive new visions of how to improve grading practices.
Includes bibliographical references and index.
Keywords: Grading and marking (Students).; Education -- Standards